Impact of the COVID-19 pandemic on the food rations of refugees in Rwanda - Emery Manirambona; Theogene Uwizeyimana; Emmanuel Uwiringiyimana; Henna Reddy (BMC, 2021)
Abstract The coronavirus disease (COVID-19) has significantly impacted the global economy, by forcing people to stay indoors and creating a 'new normal' of living. Rwanda has made notable efforts to fight the pandemic. However, the impacts of the COVID-19 pandemic on the country's economy are numerous and the refugees residing in Rwanda are not spared these effects. As of December 2020, 164,000 people were granted refugee status in Rwanda according to the United Nations High Commissioner for Refugees (UNHCR). The majority were from neighbouring countries in the Great Lakes regions, including DRC (Democratic Republic of Congo) and Burundi. The impact the COVID-19 pandemic on the global economy has led to a decline in donations to the United Nations World Food Programme (WFP), which in turn has significantly reduced the food rations of refugees. Such paucity will no doubt cause unprecedented impacts on the people residing in refugee camps, who completely depend on humanitarian aid to meet their basic food requirements. This lack of access to adequate and affordable food will expose refugees to extreme hunger and starvation, putting their lives in danger by triggering forced returns, infections, social conflicts and thus higher morbidity and mortality. Furthermore, such stressful environments would no doubt put the mental health of these already vulnerable communities at risk. It is unsurprising that refugees are more likely to experience poor mental health compared to local population, including higher rates of depression and anxiety disorders including Post-Traumatic Stress Disorder (PTSD). This is an issue as they are also less likely to receive support than the general population. Refugees in Rwanda are under the responsibility of UNHCR and WFP, who should ensure adequate food assistance is provided to refugees and therefore ameliorate the risks to health that result from food shortages, safeguarding these vulnerable communities.